Diel Variation in Abundance and Size of the South American Red Shrimp Pleoticus Muelleri (Spence Bate, 1888) (Decapoda, Solenoceridae) in the Ubatuba Region, Southeastern Brazil - Lopes, Mateus; Fransozo, Adilson; Castilho, Antonio Leão; Costa, Rogerio Caetano Da (Universidade de São Paulo, Instituto Oceanográfico, 2014)
Diel variation in the abundance and size of Pleoticus muelleri in the Ubatuba region was investigated during 2000. During each season of the year, sampling was conducted during the day and at night at 8 depths, from 5 to 40 m. The estimated number of shrimp was 955 individuals, 272 collected during the day and 683 at night. There was a difference in the abundance of P. muelleri between day and night (χ², p=2.33E-40). The abundance during the day and at night differed by season with the exception of the spring (χ², p=0.06). The abundance during both periods also differed by depth, except at 15 and 30 m, where it was not significant (χ², p=0.84 and 0.06, respectively). The shrimp caught at night were generally smaller than those caught during the day (Kolmogorov-Smirnov, p<0.01). Pleoticus muelleri juveniles were found primarily at night. This tendency could have influenced the lower mean size for this period. The sediment type and the bottom temperature appear to influence the behavior of this species and consequently the catch rate during the periods analyzed.

A variação diuturna na abundância e no tamanho de Pleoticus muelleri foi investigada na região de Ubatuba durante o ano de 2000. Em cada estação do ano, as coletas foram realizadas no período diurno e noturno em 8 profundidades, de 5 a 40 m. O número estimado de camarões foi de 955 indivíduos, 272 coletados durante o dia e 683 à noite. Houve diferença na abundância de P. muelleri entre o dia e a noite (χ², p=2.33E-40). A abundância durante o dia e à noite diferiu por estação com exceção da primavera (χ², p=0.06). A abundância em ambos os períodos também diferiu por profundidade, exceto nos 15 e 30 metros (χ², p=0.84 e 0.06, respectivamente). Os camarões capturados à noite foram geralmente menores do que os capturados durante o dia (Kolmogorov-Smirnov, p<0.01). Os juvenis de Pleoticus muelleri foram encontrados principalmente à noite e tal tendência pode ter influenciado no menor tamanho médio obtido nesse período. O tipo de sedimento e a temperatura de fundo parecem influenciar o comportamento da espécie em questão e, consequentemente, a taxa de captura durante os períodos analisados.
Keywords: Dendrobranchiata; Shrimp fisheries; Catch rate; Diurnal; Nocturnal; South Atlantic; Dendrobranchiata; Pesca camaroneira; Taxa de captura; Diurno; Noturno; Atlântico Sul